2015
DOI: 10.1007/s11427-015-4895-3
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo expansion of hematopoietic stem cells

Abstract: Ex vivo expansion of hematopoietic stem cells (HSCs) would benefit clinical applications in several aspects, to improve patient survival, utilize cord blood stem cells for adult applications, and selectively propagate stem cell populations after genetic manipulation. In this review we summarize and discuss recent advances in the culture systems of mouse and human HSCs, which include stroma/HSC co-culture, continuous perfusion and fed-batch cultures, and those supplemented with extrinsic ligands, membrane trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 197 publications
(255 reference statements)
0
11
0
Order By: Relevance
“…The detailed mechanistic pathway to reveal the exact genes or modifiers is remained to be elucidated, however, pan-inhibitors of DNA methylation are considered for preclinical and clinical application. The DNA methyltransferase inhibitors (DNMTI) including histone deacetylase (HDAC) inhibitors (valproic acid) [ 20 21 22 ], 5-aza-2'-deoxycytidine (AZA) [ 20 23 ], and nicotinamide (NAM, class3 HDAC-SIRT1 inhibitor) [ 8 20 24 ] are currently being tested for their efficacy in reducing hypermethylation of the regulatory or marker genes in hematopoiesis during ex vivo expansion. Also a large scale chemical library screening has been applied to increase long-term survival of cultured HSCs [ 20 ].…”
Section: Efforts For Ex Vivo Expansion Of Hscsmentioning
confidence: 99%
“…The detailed mechanistic pathway to reveal the exact genes or modifiers is remained to be elucidated, however, pan-inhibitors of DNA methylation are considered for preclinical and clinical application. The DNA methyltransferase inhibitors (DNMTI) including histone deacetylase (HDAC) inhibitors (valproic acid) [ 20 21 22 ], 5-aza-2'-deoxycytidine (AZA) [ 20 23 ], and nicotinamide (NAM, class3 HDAC-SIRT1 inhibitor) [ 8 20 24 ] are currently being tested for their efficacy in reducing hypermethylation of the regulatory or marker genes in hematopoiesis during ex vivo expansion. Also a large scale chemical library screening has been applied to increase long-term survival of cultured HSCs [ 20 ].…”
Section: Efforts For Ex Vivo Expansion Of Hscsmentioning
confidence: 99%
“…Transplantation of cells into irradiated immunocompromised mice remains the gold standard assay for the assessment of the repopulation capability of hematopoietic stem cells. The successful repopulation of a vacant bone marrow niche proves that the cells are native HSCs (Jingjing and ChengCheng, 2015; Nakamura-Ishizu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Co-culture of HSCs is one of the most frequently used models for understanding how the highly specific bone marrow niche interacts ex vivo with hematopoietic cells, promoting their differentiation and expansion. The technique can focus on the importance of non-contact culture systems on the successful maintenance of hematopoietic cells [47] and on the use of the stroma as a cell layer to provide support for HSC culturing, as mentioned above. Several studies have shown that contact between HSCs and stromal cells is important for maintaining HSC function [48,49].…”
Section: Stem Cell Culture Methodsmentioning
confidence: 99%